Stratosphere-troposphere exchange (STE) in the vicinity of North Atlantic cyclones - Reutter, Philipp; Škerlak, Bojan; Sprenger, Michael; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Copernicus, 2015)
ISSN:1680-7324 ISSN:1680-7375